Impact of electric generators on workers’ hearing: a case study of commercial establishments in downtown Ambato, Ecuador - Mendoza Rodríguez, José Fernando (2025)
In Ecuador, the dry season in 2024 caused problems at hydroelectric power plants due to the low water flow in the rivers. As a result of power outages, commercial establishments found it necessary to purchase generators to maintain their commercial activities. Noise measurements were conducted in 22 commercial establishments in the city of Ambato. A calibrated professional sound level meter was used for the measurements, revealing that 50% and 60% of the measurements taken in the Mercado Modelo and Teófilo López sectors, respectively, exceeded the 85 dB limit established in Executive Decree 2393. Furthermore, according to information provided by workers, it was determined that the use of electric generators led to ringing in the ears and difficulty concentrating with prevalence rates of 40.9% and 36.4%, respectively, being the most significant adverse effects.